Examination of a Structural Model of Peptidomimicry by Cyclic Acyldepsipeptide Antibiotics in Their Interaction with the ClpP Peptidase. Issue 13 (27th July 2015) - Carney, Daniel W.; Schmitz, Karl R.; Scruse, Anthony C.; Sauer, Robert T.; Sello, Jason K.
Abstract The cyclic acyldepsipeptide (ADEP) antibiotics act by binding the ClpP peptidase and dysregulating its activity. Their exocyclic N‐acylphenylalanine is thought to structurally mimic the ClpP‐binding, (I/L)GF tripeptide loop of the peptidase's accessory ATPases. We found that ADEP analogues with exocyclic N‐acyl tripeptides or dipeptides resembling the (I/L)GF motif were weak ClpP activators and had no bioactivity. In contrast, ADEP analogues possessing difluorophenylalanine N‐capped with methyl‐branched acyl groups—like the side chains of residues in the (I/L)GF motifs—were superior to the parent ADEP with respect to both ClpP activation and bioactivity. We contend that the ADEP's N‐acylphenylalanine moiety is not simply a stand‐in for the ATPases' (I/L)GF motif; it likely has physicochemical properties that are better suited for ClpP binding. Further, our finding that the methyl‐branching on the acyl group of the ADEPs improves activity opens new avenues for optimization.